A Medieval Rural Domestic Structure at Quien, Isle of Bute. Issue 1 (March 2023) - Duffy, Paul R. J.
Abstract : Archaeological investigations were undertaken at Quien, Isle of Bute in 2010 as part of the Discover Bute Landscape Partnership Scheme. Excavations demonstrated that a putative early medieval chapel in fact dates to between the 11 th and 13 th centuries AD. Associated artefacts from the surrounding enclosure bank suggest a more domestic character to the structure. An isolated pit also provided evidence of prehistoric activity in the vicinity.